2011
DOI: 10.1177/0145482x1110500607
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visual Disability on the Quality of Life of Older Persons in Rural Northeast Thailand

Abstract: This study assessed the impact of self-reported visual disability on the quality of life of older persons in rural northeast Thailand. It found that those with a visual disability were worse off on 3 of 11 quality-of-life measures than were those who were sighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
3
4
0
1
Order By: Relevance
“…Those with uncorrected refractive error, presbyopia, and visual impairment all reported a significantly lower quality of life relative to those without, indicating that the effect of such conditions is significant in their lives. These findings are in general agreement with previous studies on visual functioning and quality of life on those with cataract (Taylor et al, 2008) and refractive error (Coleman, Yu, Keeler, & Mangione, 2006;Owsley et al, 2007), and with findings that visual disabilities impact on quality of life (La Grow, Sudnongbua, & Boddy, 2011). Therefore, provision of spectacles, which is perhaps the simplest of visual health interventions, can improve vision-specific functionality, well-being, and general quality of life in those with uncorrected refractive error (Coleman et al, 2006;Owsley et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Those with uncorrected refractive error, presbyopia, and visual impairment all reported a significantly lower quality of life relative to those without, indicating that the effect of such conditions is significant in their lives. These findings are in general agreement with previous studies on visual functioning and quality of life on those with cataract (Taylor et al, 2008) and refractive error (Coleman, Yu, Keeler, & Mangione, 2006;Owsley et al, 2007), and with findings that visual disabilities impact on quality of life (La Grow, Sudnongbua, & Boddy, 2011). Therefore, provision of spectacles, which is perhaps the simplest of visual health interventions, can improve vision-specific functionality, well-being, and general quality of life in those with uncorrected refractive error (Coleman et al, 2006;Owsley et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Many foreign authors have assessed the quality of life of patients with POAG. Grow et al in their study examined respondents with deteriorated socio-economic status [ 23 ]. The study involved 190 patients with different eye diseases in the age group of 60–107 years.…”
Section: Discussionmentioning
confidence: 99%
“…43 The World Health Organization quality of life instrument, for example, defines quality of life as “an individual’s perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns.” 44,45 This instrument has been employed to gauge quality of life among people with visual impairment. 46,47 The particular effects of visual impairment, however, have led to the development of vision-specific quality of life measures. Although the Visual Function Index (VF-14) 48 and the National Eye Institute’s (NEI) Visual Function Questionnaire (VFQ-25) 49,50 are notable examples, at least 22 vision-specific instruments are available to measure activity performance and the impact of visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…51,53,66 Lee and colleagues showed that decreases in HRQoL were independently and strongly associated with the presence of visual symptoms (“trouble seeing” and “blurred vision” 16 ),a finding generally consistent with more global measures of visual impairment. 11,1719,45,46 …”
Section: Discussionmentioning
confidence: 99%